Symptoms of Poststroke Depression among Stroke Survivors: An Appraisal of Psychiatry Needs and Care during Physiotherapy Rehabilitation - Sam Chidi Ibeneme; Canice Chukwudi Anyachukwu; Akachukwu Nwosu; Georgian Chiaka Ibeneme; Muideen Bakare; Gerhard Fortwengel (Scientifica)
Purpose. To identify stroke survivors with symptoms of poststroke depression and the extent of psychiatry needs and care they have received while on physiotherapy rehabilitation. Participants. Fifty stroke survivors (22 females and 28 males) at the outpatient unit of Physiotherapy Department, University of Nigeria Teaching Hospital, Enugu, who gave their informed consent, were randomly selected. Their age range and mean age were 26–66 years and 54.76±8.79 years, respectively. Method. A multiple case study of 50 stroke survivors for symptoms of poststroke depression was done with Beck’s Depression Inventory, mini mental status examination tool, and Modified Motor Assessment Scale. The tests were performed independently by the participants except otherwise stated and scored on a scale of 0–6. Data were analyzed using Z-test for proportional significance and chi-square test for determining relationship between variables, at p<0.05. Results. Twenty-one (42.0%) stroke survivors had symptoms of PSD, which was significantly dependent on duration of stroke (χ2 = 21.680, df = 6, and p=0.001), yet none of the participants had a psychiatry review. Conclusions. Symptoms of PSD may be common in cold compared to new cases of stroke and may need psychiatry care while on physiotherapy rehabilitation.